Do high MICs predict the outcome in invasive fusariosis?. (16th December 2020) - Nucci, Marcio; Jenks, Jeffrey; Thompson, George R; Hoenigl, Martin; dos Santos, Marielle Camargo; Forghieri, Fabio; Rico, Juan Carlos; Bonuomo, Valentina; López-Soria, Leyre; Lass-Flörl, Cornelia; Candoni, Anna; Garcia-Vidal, Carolina; et al.
Abstract: Background: Invasive fusariosis (IF) affects mostly severely immunocompromised hosts and is associated with poor outcome. Since Fusarium species exhibit high MICs for most antifungal agents, this could explain the poor prognosis. However, a clear-cut correlation between MIC and outcome has not been established. Objective: To evaluate the correlation between MIC and outcome (6 week death rate) in patients with IF. Methods: We performed a multicentre retrospective study of patients with IF who received treatment and had MIC levels determined by EUCAST or CLSI for the drug(s) used during treatment. We compared the MIC50 and MIC distribution among survivors and patients who died within 6 weeks from the diagnosis of IF. Results: Among 88 patients with IF, 74 had haematological diseases. Primary treatment was monotherapy in 52 patients (voriconazole in 27) and combination therapy in 36 patients (liposomal amphotericin B + voriconazole in 23). The MIC50 and range for the five most frequent agents tested were: voriconazole 8 mg/L (range 0.5–64), amphotericin B 2 mg/L (range 0.25–64), posaconazole 16 mg/L (range 0.5–64), itraconazole 32 mg/L (range 4–64), and isavuconazole 32 mg/L (range 8–64). There was no difference in MIC50 and MIC distribution among survivors and patients who died. By contrast, persistent neutropenia and receipt of corticosteroids were strong predictors of 6 week mortality. Conclusions: Our study did not show any correlation between MIC and mortality at 6 weeks in patients with IF.